Ácido 2,3,5-tri-iodobenzoico (TIBA) na micropropagação de abacaxizeiro 'IAC Gomo-de-Mel' - Costa, Sérgio Marques [UNESP]; Fráguas, Chrystiane Borges [UNESP]; Prado, Débora Zanoni Do [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (Sociedade Brasileira de Fruticultura, 2014)
The cultivar 'IAC Gomo-de-Mel'is an economically important species due to different sensory characteristics. One of the techniques to obtain higher number of plants is micropropagation. Thus, the aim of this study was to evaluate the effects of TIBA (2,3,5 - triiodobenzoic acid) in the formation of shoots and roots of pineapple 'IAC Gomo-de-Mel ', as well as possible changes in the morphology of leaf tissues. It were used segments of the gems in the crown of pineapple, with approximately 1 cm, arising from cultivation in liquid medium supplemented with 1.0 mg L-1 BAP+ 0.5 mg L-1 NAA , and subsequently inoculated in MS liquid containing various concentrations of TIBA in light condition and controlled temperature, deploying three different experiments for biometric, biochemical and anatomical analyzes. The experiments were implanted in a completely randomized experimental design with 8 treatments and 4 replicates for biometric analysis and 5 replicates for biochemical and anatomical analysis. At the end of 60 days, were evaluated the number and length of shoots, length of the mother plant and the number of roots. The analysis of the activity of IAA-oxidase was performed on the day of the experiment and at 15, 30, 45 and 60 days of cultive. We conclude that the TIBA alone does not induce shoots formation. The reduction in the IAA-oxidase activity was related to the emission of new roots and an increase in leaf thickness occurred after exogenous application of TIBA in pineapple 'Gomo-de-Mel' cultivated in vitro.

O abacaxi 'IAC Gomo-de-Mel' é uma espécie economicamente importante devido a diversas características sensoriais. Uma das técnicas para obter maior número de plantas é a micropropagação. Assim, o objetivo deste trabalho foi avaliar a ação do TIBA (ácido 2,3,5-tri-iodobenzoico) na formação de brotos e raízes do abacaxizeiro 'IAC Gomo-de-Mel', assim como possíveis alterações na morfologia de tecidos foliares. Foram utilizados segmentos das gemas da coroa de abacaxi, com aproximadamente 1 cm, oriundos de cultivo em meio líquido, suplementadas com 1,0 mg L-1 BAP+ 0,5 mg L-1 NAA , sendo posteriormente inoculados em meio MS líquido contendo diversas concentrações de TIBA, em condição de luz e temperatura controladas, implantando 3 diferentes experimentos para as análises biométrica, bioquímica e anatômica. Os experimentos foram implantados em delineamento experimental inteiramente ao acaso, com 8 tratamentos, com 4 repetições para as análises biométricas e 5 repetições para a bioquímica e anatômica. Ao final de 60 dias, foram avaliados o número e o comprimento das brotações, o comprimento da planta-mãe e o número de raízes. A análise da atividade de AIA-oxidase foi realizada no dia da instalação do experimento e aos 15; 30; 45 e 60 dias de cultivo. Conclui-se que o TIBA isoladamente não induz brotações. A redução na atividade da AIA-oxidase foi relacionada com a emissão de novas raízes, e o aumento na espessura dos tecidos foliares ocorreu após aplicação exógena de TIBA, em abacaxizeiro in vitro.
Tiba in vitro multiplication of pineapple 'IAC Gomo-de-Mel
Keywords: abacaxi-de-gomo; AIA-oxidase; micropropagação; anatomia vegetal; pineapple-of-gomo; IAA oxidase; micropropagation; plant anatomy